Historical and geographical analysis of the Chronicle of Remmal Khodja “Tarih-i Sahib Giray Khan” - Maxim Shalak (Крымское историческое обозрение, 2021)
This article is devoted to the analysis of the historical work of the famous Ottoman scholar Muhammad Nidai Kaisuni-zade, well known as Remmal Khodja, his work “Tarih-i Sahib Giray Khan”, which was written in the middle of the XVI century. This source, is dedicated to the history of the reign of Khan Sahib Giray (1532–1551), it will be studied here for the purpose of revealing information on the historical geography of the Crimean Khanate and adjacent territories. The beginning of this analysis was published in № 2, 2018 of this journal. In his chronicle Remmal Khodja describes nine military campaigns of Sahib Giray. He describes in details the routes of movement of the Tatar troops, gives the places of crossings and location sites of the troops. Very valuable are the characteristics given by the court historian to the opponents of the khan and descriptions of the terrain on which the fighting was conducted. From the above I mentioned information, it may seem, that Remmal Khodja described the events as if he was its direct witness.